Factores protectores y de riesgo del proceso salud-enfermedad en la ruta del Qhapaq Ñan parroquia de Quinara-Loja - Acaro Morales, Ana Belén (2019)
The health protective factors are conditions, circumstances and opportunities of human beings to enhance the individual and collective health, to strengthen their capacity to undertake collective or individual actions. While, the risk factors constitute any trait, characteristic or exposure of a person, which increases the probability to get sick. The geographical space where it was investigated to correspondence to the Qhapaq-Ñan in Quinara, a pre-Inca route that contributes to the movement of inhabitants, in addition to help the commercialization, transportation of resources. Following project had the objective to describe the protective and risk factors that involved in the health-disease process in the families of Quinara Ruta Qhapaq-Ñan. It was a descriptive study of Transversal cut, with quantitative approach; It applied surveys at 50 heads of family corresponding to the sample were applied. The sociodemographic characteristics predominant the male sex in 70% of family heads and ages from 46 to 55 years old 24%, the 74% of them are in agricultural activity. The main protective factors are, vegetation and landscapes 100%, rivers, lagoons 72% and, basic services; while the risk factors are dust, climatic changes, street trash 100%, the Unified Basic Salary lower than the stipulated 52% basic needs, food 60%; Unsatisfied, health 40%, housing 42%, education 38%, recreation 32% and clothing 38%. The main cultural diseases are, Bad Air 100%, Scare 80%, Empacho 64% and Mill Fall 42%, and the conventionals: Acute Rhinopharyngitis 94%, Arterial Hypertension 40% and Diabetes Mellitus 32%.